2019
DOI: 10.3390/rs11070758
|View full text |Cite
|
Sign up to set email alerts
|

UAV-Based Photogrammetric Tree Height Measurement for Intensive Forest Monitoring

Abstract: The measurement of tree height has long been an important tree attribute for the purpose of calculating tree growth, volume, and biomass, which in turn deliver important ecological and economical information to decision makers. Tree height has traditionally been measured by indirect field-based techniques, however these methods are rarely contested. With recent advances in Unmanned Aerial Vehicle (UAV) remote sensing technologies, the possibility to acquire accurate tree heights semi-automatically has become a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
107
5
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(147 citation statements)
references
References 54 publications
(72 reference statements)
9
107
5
3
Order By: Relevance
“…Standardization and benchmarking studies focusing on data acquisition parameters are crucial to detailing best practice approaches [17]. Furthermore, one aspect common among most studies is that they implement traditional field-based measurements for validation [18]. These field surveys have also measurement errors, but the level of error is often not declared [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardization and benchmarking studies focusing on data acquisition parameters are crucial to detailing best practice approaches [17]. Furthermore, one aspect common among most studies is that they implement traditional field-based measurements for validation [18]. These field surveys have also measurement errors, but the level of error is often not declared [19].…”
Section: Introductionmentioning
confidence: 99%
“…These field surveys have also measurement errors, but the level of error is often not declared [19]. Until now, only a few studies carried out direct measurements of the length of tree trunks to verify remote sensing tree height estimates [18]. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of recent studies have confirmed the great potential of UAS photogrammetry in forest inventory, at both individual tree- [16,18] and plot-levels [14,[40][41][42][43][44][45]. In general, the quality of the obtained forest inventory data depends on the quality and accuracy of the UAS products (e.g., PCs, DSMs) and DTM, while the quality of the UAS products depends on the image block orientation method applied to UAV data, among other factors such as flight characteristics and target properties [62].…”
Section: Discussionmentioning
confidence: 91%
“…The stand consisted of 286 trees which had an average height of 17.5 m. The understorey is comprised of young European Beech (Fagus sylvatica) and Sessile Oak (Quercus petraea) sparsely dispersed throughout the stand. More information about the Britz research station can be found in Krause, Sanders, Mund, & Greve, 2019;and Krause, Strer, Mund, & Sanders, 2019.…”
Section: Study Areamentioning
confidence: 99%